2001
DOI: 10.1017/s1357729800058082
|View full text |Cite
|
Sign up to set email alerts
|

Effect of weaning age and slaughter weight on carcass and meat quality of Talaverana breed lambs raised at pasture

Abstract: Three weaning treatments (weaning at 45 days of age, at 65 days of age, unweaned) and two slaughter weights (24 and 28 kg) were compared in lambs raised at pasture, and their effect on carcass and meat traits were studied. Unweaned lambs displayed a greater growth rate, lower concentrate consumption, greater dorsal fat thickness, more kidney knob and channel fat and greater total fat levels, measured through dissection of the hind limb. Total collagen concentration was lower in unweaned lambs and the intramusc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
23
0
5

Year Published

2008
2008
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 57 publications
(35 citation statements)
references
References 34 publications
7
23
0
5
Order By: Relevance
“…The non difference on PWG of lambs weaned at different ages observed in this study is in accordance with reported on literature (CANEQUE et al, 2001) and it could be due to the fact that lambs at 60 days of age have a ruminal digestive system sufficiently developed to obtain nutrients from solid food. Beside this, ewe milk yield is very small after two months of lactation with low contribution for lamb nutrition (KARIM et al, 2000).…”
Section: Resultssupporting
confidence: 93%
“…The non difference on PWG of lambs weaned at different ages observed in this study is in accordance with reported on literature (CANEQUE et al, 2001) and it could be due to the fact that lambs at 60 days of age have a ruminal digestive system sufficiently developed to obtain nutrients from solid food. Beside this, ewe milk yield is very small after two months of lactation with low contribution for lamb nutrition (KARIM et al, 2000).…”
Section: Resultssupporting
confidence: 93%
“…For instance, Ugur et al (2004) reported non-significant influence of weaning age on weight gains of kids of Turkish Saanen goat. Also in accordance with the results of this study, Caneque (2001) and Selaive-Villarroel et al (2008) reported no effect (P>0.05) of weaning age on total lamb weight gain and daily weight gain.…”
Section: Body Weights and Weight Gainssupporting
confidence: 91%
“…Cañeque et al (2001) and Velasco et al (2004) also reported higher chilling loss in less fatty carcasses than those of fattier carcasses.…”
Section: Chilled Carcass Traits and Fat Colourmentioning
confidence: 86%